ZAKAT HASIL TAMBAK GARAM DALAM PERSPEKTIF MAQASID AL-SHARI’AH ABDUL MAJID AL-NAJJAR - Setiawan, Firman (Ahkam: Jurnal Hukum Islam, 2021)
Most of salt farmers consider the result of salt ponds are assets which are unnecessarily required to pay zakat. It iss because the result of salt ponds are not assets which are mentioned explicitly in the quran verse as assets that must be issued to zakat. Therefore, the author tries to study the zakat law from the result of salt ponds from the perspective of maqasid al-sharia by Abdul Majid al-Najjar. It is known from the result of this study that in the zakat resulting from salt ponds there is a maqasid al-kulliyah (realizing the welfare of the people and the distribution of wealth), maqasid al-nau’iyah (giving a rise to a sense of solidarity and enthusiasm to help each other between the rich and the poor), and maqasid al-juz'iyyah (purifying wealth and self, as well as cleaning charity and result of operations). The result of salt ponds are assets for which zakat must be issued and are categorized as commercial assets based on several reasons, namely: first, there are maqasid that must be realized; secondly, it is kasab; third, the result of salt ponds are not bound by the obligation of other zakat in essence; fourth, it intention/purpose to be sold; and fifth, the fulfillment of ‘illat zakat, which is al-nama’ (growing).